A Task-Based Analysis of Machinery Entanglement Injuries Among Western Canadian Farmers. - Narasimhan, Gopinath; Crowe, Trever G.; Peng, Yingwei; Hagel, Louise; Dosman, James; Pickett, William (Journal of Agromedicine)
Machinery entanglements are a leading cause of hospitalized injury on Canadian farms. This study evaluates the role farm tasks play in the occurrence of machinery entanglement events. A retrospective case series of 41 entanglement injuries involving 35 farm-machinery types was assembled. Only a few limited tasks were implicated in the majority of entanglements. These tasks were as follows: (1) field adjustments of machinery; (2) product handling and conveyance; and (3) driveline attachments and servicing. Hazards inherent and common to these tasks affected the behavior of farmers, leading to entanglements. This study establishes a need to identify hazards and assess risks associated with different tasks involving the use of farm machinery under actual field situations. Systemic changes are required to improve existing machinery safety practices through engineering, work methods, and work practice modifications. In addition to design solutions, occupational health and safetystrategies should consider activities associated with hazardous situations to inform the content of injury prevention efforts.